Accuracy of the Bilicare™ transcutaneous bilirubinometer as the predischarge screening tool for significant hyperbilirubinemia in healthy term and late preterm neonates - Peerathat Chokemungmeepisarn (2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Background: The Bilicare™ is a new device that measures transcutaneous bilirubin (TcB) level at the ear pinna. There are only few studies which have evaluated its accuracy in clinical practice. Objective: This study aims to determine the accuracy of Bilicare™ as a predischarge screening tool in late preterm and term neonates and to define the optimal cutoff point for determining the need to measure total serum bilirubin (TSB). Methods: The 35 weeks’ gestation or more and healthy neonates who underwent predischarge TSB measurement were enrolled. Bilicare™ TcB was measured within 30 minutes of blood sampling. Paired TcB and TSB data were analyzed. Results: We collected 214 paired samples. Mean age (SD) at TcB measurement was 57.17 (7.47) hours. Mean TSB (SD) was 9.79 (2.83) mg/dL. TcB showed a significant correlation with TSB (r = 0.84, r2= 0.7). The mean difference (SD) between TcB and TSB was 0.7 (0.21) mg/dL (95%CI 0.49–0.91). TcB tended to overestimate TSB level at the TSB values of <12 mg/dL but underestimate at the higher TSB level. The accuracy of using TcB values to detect neonates who required phototherapy was 92.5%. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 78.3, 94.2, 62.1, and 97.3%, respectively. If TcB +3 mg/dL was applied as a cutoff point, the sensitivity, specificity, PPV, and NPV were 100, 53.9, 20.7, and 100%, respectively. Conclusions: Bilicare™ TcB and TSB measurements were well correlated. The TcB level +3 mg/dL could detect all neonates who had significant hyperbilirubinemia requiring phototherapy during their birth hospitalization.